Hipótese da preservação de elos locais: uma explicação unificada para os déficits de produção e compreensão no agramatismo (Revista de Estudos da Linguagem, 2006)
The goal of this paper is to discuss the relevance of studies of aphasicsyndromes to linguistic theory. This will be done by analyzingthe main features involving the definition and the work withagrammatism. Two main ideas will be defended: that agrammatismis an aphasic syndrome in which both linguistic production andcomprehension are affected and that there are regular observablepatterns in the disruption of these two modalities. It will be arguedthat these ideas can serve as the basis for the elaboration of ahypothesis that accounts in a unified manner for the deficitsobserved in agrammatism. This hypothesis, named “Preservationof Local Links”, claims that only links that are local in grammar arepreserved in agrammatism, while any other kind of non-local linkis to be considered disrupted. In this way, the presentation ofsuch hypothesis is a contribution to the dialogue that studies ofaphasic syndromes can entertain with linguistic theories.